Regionale Steuerung der Energiewende in Nordostdeutschland - Innovationen im Planungssystem? - Ludger Gailing; Petra Overwien; Matthias Plehn; Nadin Gaasch; Henry Lewerentz; Robert Riechel; Andrea Bues; Matthias Naumann; Jens Hoffmann (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2021)
Nordostdeutschland ist einer der räumlichen "Hotspots" der deutschen Energiewende für die Windkraft an Land wie auch für andere Anlagen erneuerbarer Stromproduktion. In Brandenburg und Mecklenburg-Vorpommern wurden dazu in den letzten Jahren vielfältige Erfahrungen gesammelt und Herausforderungen seitens der Regionalplanung gemeistert. Der Forschungsbericht analysiert dieses dynamische Themenfeld aus der Perspektive der Innovationsforschung. Ansätze der Innovationsforschung werden vorgestellt und auf ihre Relevanz für die Analyse des Planungssystems diskutiert, Rahmenbedingungen der regionalen Steuerung der Energiewende in Bund und Ländern werden beschrieben. Diskussionen mit Fokusgruppen untermauern die Betrachtungen empirisch. Der Forschungsbericht macht sichtbar, welche Beiträge die Regionalplanung zu den Erfolgen insbesondere im Windkraftausbau der letzten Jahre geleistet hat. Wenngleich Akteure der Regionalplanung sich in ihrer traditionellen Selbstbeschreibung nicht unbedingt als innovativ verstehen, sind sie sich aber bewusst, dass sie an tiefgreifenden Veränderungen mitwirken. – – Northeast Germany is one of the spatial "hotspots" of the German energy transition for onshore wind power as well as for other renewable electricity production facilities. Regional Planning in Brandenburg and Mecklenburg-Western Pomerania gained a wide range of experience in recent years and mastered respective challenges. This report analyses this dynamic topic area from the perspective of innovation research. It presents and discusses approaches of innovation regarding their relevance for the analysis of the planning system; it explains framework conditions of the regional control of the energy transition in the federal and state governments. Discussions with focus groups provided empirical support for the observations. The report enlightens the contributions of regional planning to the successes of recent years, especially in the expansion of wind power. Although actors in regional planning do not necessarily see themselves as innovative in their traditional self-description, they are aware that they are involved in profound changes. The title of this report evokes the question about the innovative power of regional planning. In general, we can answer this question in a positive way. We detected atmospheres of innovativeness in supra-local spatial planning in terms of informal moderation of social negotiation processes, with regard to the development of goals and guiding principles, but also in the transformation of formal regional planning processes. This necessary transformation did not only follow a top-down approach, but was actively promoted at all levels of the planning system. Hence, the challenging transformation process of the energy transition was not only a conflict driver, but also an "innovation driver". It created a climate of innovation in the field of action of regional planning.
urn:nbn:de:0156-10583
Keywords: 710; Energiewende; Innovationen; Regionalplanung; Regionalentwicklung; Innovationstheorie; Energy transition; innovations; regional planning; regional development; innovation theory